Загальні правила комунікації студента з пацієнтом - Khaustova Олена (Psychosomatic Medicine and General Practice, 2019)
The role of the doctor in any society carries a powerful social burden, so it is clear that for the vast majority of medical students, the initial steps in learning to communicate with patients in this new role for them are quite alarming. That is why in the beginning there are many questions about the features of professional medical communication, students ask themselves and their teachers when they begin training in the communicative skills of a doctor. For most students, the initial steps of learning how to communicate with a patient are very disturbing and uncomfortable. It is usually difficult for students to understand why a patient has to agree to communicate with them or what is “worse”, has to agree to a student’s examination. Some students feel uncomfortable because they think that patients will feel humiliated if they have to interview with a student. Some may find communication with sad patients so uncomfortable that it is further a matter for patients to express their concerns. This is primarily due to the strong physician`s social role in the society to which junior medical students are not ready both in terms of professional competence and personal psychological maturity. That is why so many questions arise at the beginning about the peculiarities of professional medical communication that students ask themselves and their teachers when they begin learning physician communication skills. Students should begin to learn how to respond and communicate in such a way that it is useful and supportive for patients, to master strategies for handling complicated communication situations. The article provides answers to the most common questions of concern to students about communicating with patients, illustrated with examples of different communication situations. Features of communication with the patient in different situations are described: at the acquaintance, at the beginning of the examination, in cases when the patient asks questions about diagnosis, course of disease and treatment, when during communication he suffers from pain or emotional stress, starts crying or showing dissatisfaction, refuses to submit clinical interview, reports on medical information, thoughts, experiences, and complaints not shared with physicians.